Análise de microRNAs (miRNAs) em Líquen Plano Bucal - Telma Cristina Arao (2011)
Oral lichen planus (OLP) is a chronic inflammatory disease that is Th1-mediated and affects the oral mucosa with a variety of clinical presentations. Interferon-gamma (IFN-) is an important cytokine involved in the regulation of local immune response in OLP. MicroRNAs (miRNAs) are small non-coding RNA molecules whose function is the post-transcriptional regulation of certain subsets of mRNAs. Recently, some studies have demonstrated that miRNAs participate in immune system regulation. Considering that increased IFN- expression is possibly associated with OLP pathogenesis and may be influenced by the action of miRNA-146a and miRNA-155, the purpose of the present study was to investigate the expression of these miRNAs together with its association with IFN- expression in OLP lesions. Quantitative Real-Time polymerase chain reaction (qRT-PCR) was used to verify the relative quantification of miRNA-146a and miRNA-155 in 31 OLP samples and 6 normal mucosa samples. ELISA assay also was performed to determine the IFN- levels in some OLP samples. The results showed that the relative quantification of miRNA-146a and miRNA-155 was higher in OLP than in normal oral mucosa (p = 0.0120 and p = 0.0031, respectively). However, both the miRNAs were not correlated with the IFN- levels. In conclusion, our study brings to light the possibility of miRNA-146a and miRNA-155 involvement in the regulation of the immune response in OLP. Nevertheless, further studies are necessary to establish the functional significance of these findings in OLP development.